The Role of Educational Interventions in Mitigating Hypertension Among the Elderly: A Systematic Review - Ake Royke Calvin Langingi; Mareyke Yolanda Lusia Sepang; Meylani Dewi Wowor; Ignatia Yohana Rembet; Stella Rasu; Priscila Evangelin Asa; James Komaling; Ifka Wangi Kobis (Postgraduate, University of Mataram, 2025)
Hypertension is one of the most common major health problems in the elderly population and is a major cause of global morbidity and mortality. Factors such as aging, unhealthy lifestyles, low medication adherence, and the presence of comorbidities contribute significantly to the increase in hypertension in the elderly. This study aims to analyze factors associated with hypertension in the elderly, including demographic, lifestyle, and medical factors, through a systematic review (SR) approach. The study was conducted by searching scientific literature from various reputable databases published between 2019 and 2025, using inclusion criteria that included the elderly population, blood pressure measurements, and the identification of relevant risk factors. The synthesis results indicate that demographic factors such as advanced age and female gender, lifestyle factors such as high salt consumption, low physical activity, and smoking habits, and medical factors such as family history of hypertension, medication adherence, and the presence of comorbidities (especially diabetes and heart disease) are the main determinants of the degree of hypertension in the elderly. Non-adherence to medication contributes to the severity of hypertension, wheres adherence contributes to the control of hypertension.